INCONSISTENCIES AND CONTRADICTIONS IN TARGUM PSEUDO-JONATHAN: THE CASE OF ELIEZER AND NIMROD - Hayward, Robert (Journal of Semitic studies, 1992)
C.T.R. Hayward; INCONSISTENCIES AND CONTRADICTIONS IN TARGUM PSEUDO-JONATHAN: THE CASE OF ELIEZER AND NIMROD, Journal of Semitic Studies, Volume XXXVII, Issue 1